Two new species of cascudinhos of the genus Otothyropsis (Siluriformes: Hypoptopomatinae) from the rio Paraná basin, Brazil - Calegari, Bárbara B.; A., Pablo Lehmann; Reis, Roberto E (Zootaxa, 2013)
Otothyropsis polyodon, sp. n., and O. biamnicus, sp. n., two new species of loricariid catfishes are described from the rio Paraná basin. Otothyropsis biamnicus and O. polyodon differ from two other Otothyropsis by having a longer caudal peduncle, middle series of lateral plates complete and with higher number of plates, and the anterior margin of the mesethmoid not covered by median rostral plate ventrally. The new species differ from each other in that O. polyodon have a longer pectoral-fin spine and a greater number of premaxillary and dentary teeth. Otothyropsis polyodon was collected in the rio Verde, tributary to the upper rio Paraná basin, and O. biamnicus is found in both the rio Iguaçu and rio Tibagi basins. A key for the species of Otothyropsis is presented and their relationships and geographical distributions are discussed.